Prevalência de colonização por Streptococcus do grupo B entre gestantes ou parturientes atendidas no Hospital de Base de São José do Rio Preto/SP - Jorge, Luciana Souza (2005)
Since the 1970´s Group B Streptococcus (GBS) or Streptococcus agalactiae has been considered the leading cause of early-onset neonatal disease. Even after the adoption of strategies for intrapartum antimicrobial prophylaxis (IAP) in the 1990´s, it has been observed GBS to be responsible for approximately 70% of neonatal mortality. The objective of this study was to establish prevalence of GBS colonization among pregnant women and parturients treated at Hospital de Base de Sao Jose do Rio Preto and the perinatal factors of risk related to maternal colonization. A descriptive and retrospective study was carried out. One hundred and twenty-two patients (pregnant women and parturients) selected for risk factors were submitted to collection of vaginal and rectal swabs which were then inoculated to specific Todd-Hewitt broth used to GBS identification. Statistical analysis of data was performed using logistic regression and Pearson 2 test or Fisher´s test, as appropriated. Prevalence of GBS maternal colonization was 24.6%, revealing statistically significant evidence among women with school education between 8 and 11 years (p=0.029) and those referring having had previous infant born with neonatal disease (p=0.025). The prevalence of GBS colonization of patients admitted at the studied Hospital Obstetrics Department points out the necessity for the institution to have an IAP protocol in order to avoid indiscriminate use of antimicrobial therapy for newborns admitted at the Neonatal Intensive Therapy Unit (NITU) and reduce the rate of neonatal morbidity and mortality.